Neutron Embrittlement of WWER Reactors: EC-Supported Projects - Ahlstrand, R.; Bieth, M.; Rieg, C. (Проблемы прочности, 2004)
Results of the implementation of programs on the evaluation of service life of reactor pressure vessels of NPP are considered with the account of neutron embrittlement. Data on strength of WWER-440 reactor pressure vessels with a high and moderate content of detrimental impurities (copper and phosphor) have been analyzed. For the welds of WWER-1000 reactor, drawbacks in the manufacture, dosimetry, and test procedures of surveillance specimens are shown. To ensure safe operations of reactor pressure vessels, new projects have been undertaken, focusing on the effect of neutron embrittlement of steel on the integrity of structures and advanced experimental methods of studying material strength. Представлены результаты исследований по определению ресурса корпусных сталей АЭС с учетом радиационного охрупчивания. Проанализированы данные по изучению прочности корпусов реакторов ВВЭР-440 с высоким и умеренным содержанием вредных примесей (медь и фосфор) в стали. Для сварных соединений отмечены недостатки процедуры испытаний образцов-свидетелей, технологии их изготовления, нейтронной дозиметрии. С целью обеспечения надежной эксплуатации корпусов реакторов разработаны новые проекты, направленные на изучение влияния радиационного охрупчивания сталей на структурную целостность и усовершенствование экспериментальных методов оценки прочности материалов. Представлено результати досліджень щодо визначення ресурсу корпусних сталей AEC з урахуванням радіаційного окрихчення. Проаналізовано дані про міцність корпусів реакторів BBEP-440 із високим і помірним вмістом шкідливих домішок (мідь і фарфор) у сталі. Для зварних з ’єднань відмічено недоліки процедури випробувань зразків-свідків, технології їх виготовлення, нейтронної дозиметрії. Із метою забезпечення надійної експлуатації корпусів реакторів розроблено нові проекти, що направлені на вивчення впливу радіаційного окрихчування сталей на структурну цілісність та удосконалення експериментальних методів оцінки міцності матеріалів.